(untitled) (The Review of Diabetic Studies, 2024)
Diabetic ketoacidosis (DKA) is a serious and perhaps deadly short-term effect of diabetes mellitus that needs to be diagnosed and treated very away. Insulin deficiency, infections, or physiological stress can induce this syndrome, characterized by hyperglycemia, metabolic acidosis, and ketosis. This case-based discussion paper shows how important critical care nursing is for taking care of a critically ill patient with DKA. We focus on completing complete evaluations using the ABCDE framework, swiftly finding the most important concerns, establishing correct nursing diagnoses, and putting together a treatment plan based on evidence. Fluid resuscitation, insulin therapy for an indefinite period, monitoring of acid-base balance and electrolytes, patient-centered education, and prevention of complications were essential nursing interventions. Stabilizing hemodynamics, normalizing metabolism, and enhancing neurological state necessitated interdisciplinary collaboration and continuous evaluation. This case study shows how crucial nurses are in getting the best clinical results and stopping DKA from coming back by teaching patients and carefully organizing their departure.